三元乙丙橡胶为基材的高模量汽车V带的研究 - 陈民杰 (Jixie chuandong)
With the increase of working temperature around auto engine,CR based V-belts（Including automotive V-ribbed belts） can not meet the requirement anymore,and the EPDM is the best substitute,the EPDM parameters effect on V-belts mechanical property is investigated.ZDMA is used to reinforce EPDM to prepare high modulus V-belts,and the ZDMA effect on adhesion between EPDM and fabric is investigated.